Video Game to Help in Movement Rehabilitation - Neto, João Graça; Kronbauer, Artur Henrique; Barreto, Shirley Gois (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
The medical area has benefitted from several technological innovations over the years. A good example of this is the development of video games with natural interaction that can aid in physical and occupational therapy treatments. This article introduces a new alternative in this area with an infrastructure that contains: (i) an environment that facilitates the development of games; (ii) an inexpensive video game console, and (iii) an innovative wearable control. Preliminary usability experiments were done with users and professionals from the medical field. Promising results were obtained for both parties.